The big book of Australian history - Macinnis, Peter; National Library of Australia (Canberra : National Library of Australia, 2015)
This is the second edition of 'The big book of Australian history', awarded 'Notable Book' by the Children's Book Council of Australia in 2014. Drawing on the impressive collections of the National Library of Australia, this comprehensive book provides children with an interesting and engaging overview of the history of Australia. It covers many of the main events in the nation's history. Packed with colourful images and interesting facts, 'The big book of Australian history' introduces children to the many people and events that have made Australia what it is today. It also encourages them to think about how Australia has evolved as a nation.
"Notable Book. The Children's Book Council of Australia"--cover.
National Library's copies signed by author.
Includes index.
Cultural sensitivity advisory notice: Aboriginal, Torres Strait Islander and other First Nations people are advised that this item may contain names, recordings, images of deceased people and other content that may be culturally sensitive.
For upper primary school age.
Keywords: Discoveries in geography; Social history; Politics and Government - Political action - Land rights; Politics and Government - National symbols and events - Apologies; Race relations - Violent - Massacres, murders, poisonings etc. - To 1900.; Sport; Settlement and contacts - Colonisation; Art - Rock art; Politics and Government - Political action - Anti racism; Australia -- History -- Juvenile literature; Australia -- Social conditions -- Juvenile literature; Australia -- Discovery and exploration -- Juvenile literature; Australia; Myall Creek (N NSW SH56-05); Tasmania (Tas); Australian; History; Juvenile works